The Influence of Social Media Marketing on Instagram on the Decision to Purchase Thrift Fashion Products (Study of Followers of the Instagram Account @Sechondshop.co) - Agnesia Sulastri Aru; Moch. Nurhidayat; Fitria Setyaningrum (International Journal of Management and Business, 2026)
This study aims to analyze the influence of social media marketing on Instagram on thrift fashion product purchasing decisions among followers of the account @Sechondshop.co. The study used a quantitative approach with an explanatory method. The study population was active followers of the account @Sechondshop.co, using a non-probability sampling technique. Data were collected through a questionnaire and analyzed using simple linear regression. The results of the study indicate that social media marketing has a positive and significant influence on purchasing decisions, as evidenced by a t-test with a calculated t-value greater than the t-table. The coefficient of determination (R²) of 0.755 indicates that social media marketing influences purchasing decisions by 75.5%, while the remainder is influenced by other factors outside the study. This finding confirms that social media marketing through Instagram plays a significant role in driving purchasing decisions for thrift fashion products among followers of the @Sechondshop.co account.